UPAYA PEMERINTAH DAERAH DALAM MENINGKATKAN KEDISIPLINAN PEGAWAI (STUDI PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SDM KABUPATEN BURU SELATAN) - RAMLI, ARIYANI (Patria Artha University, 2021)
The purpose of this research was to divulge the factors that caused the low discipline of employees in the Office of the human resources and employment agencies at the City of Buru Selatan Islands, and government efforts in tackling the low discipline of emplo yees in the human resources and employment agencies office of Buru Selatan city.The research informants were 6 people consist of the head of the office, Head of the human resources training and development division, head of sub-division personnel, and three staffs in the human resources and employment agencies office of Buru Selatan city. The approach in this study was explorative method with an inductive approach, essentially looking for understanding obtained from facts and data in the field. Data collection techniques in this study were through observation, interviews, and documentation.Research and discussion results obtained efforts that will accomplished by the local government in order to improve the discipline of employees of the human resources andemployment agencies office at the city of Buru Selatan islands, namely the Implementation of Government Regulation Number 53 of 2010 concerning discipline of civil servants consistently, making rules governing reward and punishment, strengthening the basic commitment of each individual in implementing discipline in carrying out the organization's vision and mission, and increasing supervision of civil servant discipline.